Media Komunikasi dalam Peran Dakwah - Effendy, Erwan; Karsita, Muhammad Faruq; Harahap, Sylvia Amalia; Syakira, Nayaka; Aini, Azizah; Khairunnisa, Farida (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
The method of preaching has changed over time. Written sermons are now more important and effective than oral sermons, especially in works that contain preaching messages and social media. This is in line with the saying of the Prophet Muhammad, "Indeed, the ink of the scholars is better than the blood of the martyrs," which shows that the content of preaching will not be lost even if the preacher or writer has passed away. This study aims to analyze the impact of media on the growth of Islamic preaching. The research strategy uses a qualitative method based on field data. When Allah SWT says in the Qur'an, Saba':28, "And We have not sent you, [O Muhammad], except as a bringer of good tidings and a warner to all mankind, but most of the people do not know," it is clear that He obliges preaching to others. The results of the study in this paper show that the use of mass media as a channel for preaching offers benefits, demonstrating the importance of media involvement in spreading religious beliefs among the public.